Fa’aliyyah Lu’bah As-Sunduq As-Sirriy Litarqiyyah Maharah Kalam At-Tullab Fi Al-Madrasah Ad-Diniyyah Awwaliyah Muhammadiyyah Siamang Buni - Novrilla, Wahyu; Zubaidah, Zubaidah; Husni, Arman; Hayati, Hayati; Hasanah, Nur; Febriyanti, Rita (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
The background of the research on learning speaking skills of students in Madrasah Diniyyah Awaliyah Muhammadiyyah (MDAM) Siamang Bunyi, thought the game, namely secret the box game, to increase student activity in speaking skills. Because learning media is only textbook and blackboard media at school, only students pay less attention, so many do not achieve completeness. So researchers are interested in researching this problem. Researchers use quantitative research, namely the method of collecting data using interviews and exams. As for the exam, there are two pretest and posttests to see whether the media used can improve students learning outcomes or not